Dual-frequency altimeter signal from Envisat on the Amery ice-shelf - Lacroix, P; Legresy, B; Coleman, R; Dechambre, M; Remy, F (Remote Sensing of Environment, 2007)
In Antarctica, radar altimeter measurements are sensitive to dielectric and penetration properties of the sensed medium (snow) such that the spacecraft's altitude can be biased. Since 2002, relatively low frequency radar measurements over the Amery Ice Shelf, east Antarctica, have been acquired using the Envisat dual frequency altimeter at S (3.2GHz) and Ku (13.6GHz) bands, which penetrate a few meters into the firn. The altimeter signal is however modified in summer by the presence of snowfilled crevasses. Indeed, the specularity of the snow surfaces in summer makes the altimetric signal sensitive mostly to nadir echoes, that increases the ratio between the crevasse signal and the surrounding ice-shelf signal at nadir. Crevasses are distinguished by differences in backscattering behavior compared with the surrounding ice-shelf signal. Crevasses are characterized by a strong backscatter coefficient at Ku band and anomalies in the S band altitude estimation. These two characteristics make snowfilled crevasses detectable by the dual frequency altimeter of Envisat. We first retrieve the geometric properties of the crevasses using a hyperbolic shape function, created by strong crevasse backscatter in the Ku waveform measurements. From this retrieved crevasse signal and further waveform analysis, we assess the properties of the snow surface and its sub-surface. The crevasse, due to its small size compared to the altimeter footprint, is found to be an excellent target to study snow properties of the ice-shelf. The anomalies in the S band altitude measurements over crevasses can then be explained by the presence of a double echo in the S band waveforms. This echo is attributed to a reflection at the base of the snowbridge, where we see evidence of sub-surface echos in the individual altimeter waveforms. Based on this observation, a methodology is developed to estimate the thickness of the snowbridge. We calculate the penetration depths in the summer snow surface of the Amery at Ku band, that is found to be around 6m. 2007 Elsevier Inc. All rights reserved.